Some psychoanalytic considerations about psychoses (Research, Society and Development, 2022)
This article aims to discuss some theoretical considerations about psychoses based on psychoanalysis. The methodology used is psychoanalytic research based on a literature review. The difference between psychiatric science and psychoanalysis is presented, which opens another treatment proposal in the direction of the incidence of the unconscious. The Name-of-the-Father and the paternal metaphor are discussed as fundamental theoretical formulations for thinking about psychic functioning in psychosis. Emphasizing that the Name-of-the-Father is the support of the symbolic function, which makes the law - sustained by the symbolic father - operate in its incidence of the phallic signifier, being what is left out, what is foreclosed, in psychosis. In conclusion, it is considered that Lacan, in his reinterpretation of Freud, advances in the question of the treatment of the psychotic patient. The fundamental importance of his theoretical-clinical elaborations in psychoses is highlighted, which says that madness is a proper functioning that breaks with this possibility of addressing the Other, but that can be heard in its condition as a subject who participates in language differently, in its delusional and hallucinatory constructions. Lacan summons analysts to work with this clinic, in the direction of his teaching and transmission, maintaining the question of what is possible in the treatment. We bet on work, as much as possible, for each patient and each analyst.